The Technology Imperative of the Cree: Examining Adaptability and Livelihood in Northern Ontario, Canada - Lemelin, Raynald Harvey; Beaulieu, Michel S. (Journal of Northern Studies, 2014)
In this article we discuss how the incorporation of selected technologies (i.e., outboard motor, snowmobile) in Northern Ontario profoundly and irrevocably transformed two Cree nations located in the Hudson Bay Lowlands. We demonstrate how this technological integration has provided two remote First Nations in Canada with the ability to adapt to biophysical and socio-cultural changes, thereby sustaining traditional livelihood and providing food security. Interviews conducted in 2006–2010 with the Weenusk First Nation at Peawanuck, and the Washaho First Nation at Fort Severn are used to contextualize the discussion and answer the following research questions: (a) Are a greater or smaller number of people in these two First Nations engaged in subsistence behaviour today than in the past?; (b) Are these harvesters more or less successful?; and (c) Are levels of subsistence consumption different? The findings indicate that while less people are generally participating in traditional subsistence activities, access to traditional foods due to technology remains, for the time being, the same. The sustainability of these activities on the long-term is examined in the conclusion.